Christian spirituality in dialogue with secular and African spiritualities with reference to moral formation and agency - Kretzschmar, Louise (Theologia Viatorum, 2008)
This article notes the need for personal and communal moral renewal in South Africa and asks what contribution Secular, African and Christian spiritualities can make in this regard. A dialogue with Secular and African Spirituality from the perspective of Christian Spirituality is embarked upon with reference to spiritual and moral paradigms, personal moral character and moral agency within communities. I seek to evaluate both the strengths and weaknesses of these three spiritualities and to identify what they can learn from one another in the task of effecting moral renewal in South Africa.
free